2008
DOI: 10.1186/1471-2091-9-3
|View full text |Cite
|
Sign up to set email alerts
|

Blocking binding of Bacillus thuringiensis Cry1Aa to Bombyx mori cadherin receptor results in only a minor reduction of toxicity

Abstract: Background: Bacillus thuringiensis Cry1Aa insecticidal protein is the most active known B. thuringiensis toxin against the forest insect pest Lymantria dispar (gypsy moth), unfortunately it is also highly toxic against the non-target insect Bombyx mori (silk worm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Finally, an anti-Bt-R 175 antibody protected detached B. mori midgut cells from Cry1Aa toxin, as judged by the analysis of the release of lactate dehydrogenase activity after exposure of the cells to Cry1Aa toxin [48,49]. Nevertheless, a Cry1Aa mutant (F328A) that showed 23-fold reduced binding to Bt-R 175 was shown to have only a 4-fold reduction in the toxicity to B. mori larvae, suggesting that an additional protein in the larval gut could in part fulfill the role of Bt-R 175 in this insect species [50].…”
Section: Expression Of Cadherin Receptors In Cell Linesmentioning
confidence: 92%
“…Finally, an anti-Bt-R 175 antibody protected detached B. mori midgut cells from Cry1Aa toxin, as judged by the analysis of the release of lactate dehydrogenase activity after exposure of the cells to Cry1Aa toxin [48,49]. Nevertheless, a Cry1Aa mutant (F328A) that showed 23-fold reduced binding to Bt-R 175 was shown to have only a 4-fold reduction in the toxicity to B. mori larvae, suggesting that an additional protein in the larval gut could in part fulfill the role of Bt-R 175 in this insect species [50].…”
Section: Expression Of Cadherin Receptors In Cell Linesmentioning
confidence: 92%
“…Nevertheless, Cry1Ac mutants in domain III that are affected in binding to APN-1 had a marginal effect on toxicity against M. sexta larvae (23). Also, in the case of Bombyx mori, it was shown that anti-cadherin antibodies protected detached midgut cells from the toxic effects of Cry1Aa, in contrast to anti-APN antibodies that had no effect on the toxicity of Cry1Aa (24). These apparently contradictory data could be explained if an additional secondary receptor could play the same role as APN in M. sexta midgut cells.…”
mentioning
confidence: 99%
“…Nevertheless, some Cry1Ac mutants affected in binding to APN1 showed a marginal effect on toxicity against M. sexta larvae, suggesting that other Cry1Ac binding proteins may be involved in Cry1Ac toxicity (16). In the case of Bombyx mori, it was shown that anticadherin antibodies protected detached midgut cells from the toxic effects of Cry1Aa, in contrast to anti-APN antibodies, which had no effect on the toxicity of this toxin (17). These apparently contradictory data could be explained if an additional secondary receptor could play the same role as APN in midgut cells.…”
mentioning
confidence: 99%